2021
DOI: 10.1063/5.0031260
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics modeling of the initiating capability of detonators. II. Booster initiation

Abstract: Detonators are explosive devices used for the initiation of secondary explosives in commercial and military applications. They are characterized by their initiating capability which is a critical factor for their safe and effective use but challenging to assess accurately. In this two-part study, we employ numerical simulations to investigate the blast wave generated by detonators and examine their initiating capability. The first part follows the European underwater test which evaluates detonators in isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…As the detonation travels faster than the inert shock, it eventually reaches the vertical wall of the rigid well, producing a region within the explosive sample where no reactions have occurred; this results in a dead zone that is observed to persist for the rest of the simulation. The results are in good agreement with the study by DeOliveira et al [12] and the numerical solutions reported in Ioannou and Nikiforakis [16], where high pressure LX-17 products are used to initiate the main sample of explosive. Indeed, the use of UF-TATB products does not qualitatively affect the overall results, but illustrates the applicability of the proposed model to scenarios involving two distinct explosive materials.…”
Section: Numerical Results In the Presence Of Two Reactive Materials ...supporting
confidence: 91%
See 2 more Smart Citations
“…As the detonation travels faster than the inert shock, it eventually reaches the vertical wall of the rigid well, producing a region within the explosive sample where no reactions have occurred; this results in a dead zone that is observed to persist for the rest of the simulation. The results are in good agreement with the study by DeOliveira et al [12] and the numerical solutions reported in Ioannou and Nikiforakis [16], where high pressure LX-17 products are used to initiate the main sample of explosive. Indeed, the use of UF-TATB products does not qualitatively affect the overall results, but illustrates the applicability of the proposed model to scenarios involving two distinct explosive materials.…”
Section: Numerical Results In the Presence Of Two Reactive Materials ...supporting
confidence: 91%
“…In order to capture desensitisation effects and the formation of dead zones, the desensitisation model proposed by DeOliveira et al [12] is included in the formulation with the same parameters used therein. The computational domain is discretised with a coarse mesh of size 160 mm and two levels of refinement, with refinement factors ×4 and ×2 are used to adaptively increase the resolution around the detonation front, material interfaces and rigid boundaries; this results in an effective resolution of ∆x = ∆y = 20 µm which is consistent with that used by Ioannou and Nikiforakis [16]. Numerical results are shown in Fig.…”
Section: Numerical Results In the Presence Of Two Reactive Materials ...mentioning
confidence: 90%
See 1 more Smart Citation